ANALISIS ARAH KEBIJAKAN SEKOLAH TERHADAP PENGGUNAAN GADGET SEBAGAI MEDIA PEMBELAJARAN DI SD N 3 KUTACANE - Sari, Purnama; Iqbal, Muhammad; Iskandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This thesis research examines the policy of SD N 3 Kutacane regarding the use of Gadget s in the learning process. To address the research questions posed in this thesis, a qualitative research method with a phenomenological approach was employed. The findings reveal that, first, the use of Gadget s in learning significantly aids in deepening students' understanding of material that they have not yet grasped. Gadget s are also used in the classroom, but not excessively, as teachers prioritize books over Gadget s. The use of Gadget s is more emphasized for home learning, monitored by the teaching staff, with sanctions applied to any violations. At SD N 3 Kutacane, Gadget s are also used for completing assignments and expanding students' knowledge, making them more creative, innovative, and technologically adept. The policy allows students to bring and operate Gadget s at school with certain restrictions. Gadget s must not be used during class time unless permitted by the teacher and with parental consent. In addition to being a learning tool, Gadget s are also used for communication between teachers, students, and parents. Parental involvement is crucial in overseeing Gadget  use at home to maintain balance and support the child's psychosocial development. Parents are expected to guide and limit Gadget  use, providing restricted permissions to ensure children do not overuse them, thus supporting their education and optimal development.